2020
DOI: 10.3390/su12197970
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts on a Tropical Fishery Ecosystem: Implications and Societal Responses

Abstract: The present study aimed to map out the current threats and anticipated impacts of climate change on the most important hilsa shad (Tenualosa ilisha) fishery and the associated fishing communities based on fieldwork in six coastal fishing communities. To collect empirical data, individual interviews, focus group discussions, oral history, and key informant interviews were conducted. To supplement the empirical findings, time-series data of cyclones and sea-borne depressions in the Bay of Bengal were also analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…The small-scale coastal fisheries support the livelihoods of half of a million fisherfolk and their household members, who catch almost 82% of the total marine caught in Bangladesh (DoF, 2018). Bangladesh and its fisheries sector are victims of global climate variability and change (BBS, 2020; Islam et al , 2020). Different climatic variables, including tropical cyclone and storm surge, salinity, sea-level rise, water temperature, rainfall and drought, have adverse effects on coastal fishing productivity, affecting the fishing community’s livelihood and overall well-being (Alam et al , 2018; Vivekanandan et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The small-scale coastal fisheries support the livelihoods of half of a million fisherfolk and their household members, who catch almost 82% of the total marine caught in Bangladesh (DoF, 2018). Bangladesh and its fisheries sector are victims of global climate variability and change (BBS, 2020; Islam et al , 2020). Different climatic variables, including tropical cyclone and storm surge, salinity, sea-level rise, water temperature, rainfall and drought, have adverse effects on coastal fishing productivity, affecting the fishing community’s livelihood and overall well-being (Alam et al , 2018; Vivekanandan et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…MPAs will continue to be useful as they provide a clearly defined geographical space managed by communities or the government dedicated toward long-term conservation of marine and fisheries resources (Cabral et al, 2014). Admittedly, to mitigate climate change impacts with economic and ecological effects there need to be development assistance in protecting fishers' well-being, prioritizing alternative livelihoods, technical skills trainings and increasing value to their fisheries products to enhance their resilience to external shocks (Islam et al, 2020;Suh and Pomeroy, 2020). This would be in addition to the on-going work of conservation of coral reefs, seagrass, mangroves and coastal wetlands which are known to protect coastal communities during extreme events (McClanahan et al, 2008;Lee et al, 2014;Sun and Carson, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Islam et al (2020) was embraced to evaluate the impacts of climate alter on the hilsa shad fishery system and the versatile measures taken by fisher communities in Bangladesh's coastal locale. It found that climate alter has colossal unfavorable effects on the country's most impoverished fishing communities by affecting their job resources, particularly by diminishing the hilsa stock upon which their employments are based.…”
Section: Literature Review Impact On Climate Change On Small Scale Fishersmentioning
confidence: 99%